STRATEGI PENGEMBANGAN POTENSI WISATA BERBASIS WELLNESS TOURISM DI TAMAN WISATA ALAM GUNUNG PANCAR - Adinda Alya Farhanny; Nungky Puspita; Hindun Nurhidayati (Kepariwisataan: Jurnal Ilmiah, 2026)
AbstractThis study analyzes the tourism potential and implementation of wellness tourism at Mount Pancar Natural Tourist Park and formulates a development strategy based on SWOT analysis. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving stakeholders from KSDA Resort Region IV Bogor, PT Wana Wisata Indah, village officials, local community representatives, and tourists. Data analysis was conducted using SWOT, supported by IFE and EFE matrices with weightings and ratings validated through expert judgment and stakeholder triangulation. Results show a total IFE score of 3.04 and EFE score of 2.93, positioning the park in Quadrant I, which necessitates an aggressive growth strategy that leverages strengths and opportunities to mitigate weaknesses and threats. This research addresses the gap in tailored wellness tourism development models for conserved natural parks in peri-urban settings. Practical implications include prioritizing the revival of structured healing forest programs, enhancing accessibility, and strengthening community-based wellness amenities to elevate the park’s competitiveness as a leading wellness tourism destination.AbstrakPenelitian ini bertujuan menganalisis potensi dan implementasi wellness tourism serta menyusun strategi pengembangannya di Taman Wisata Alam (TWA) Gunung Pancar. Metode yang digunakan adalah deskriptif kualitatif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi terhadap pengelola (KSDA Resor Wilayah IV Bogor dan PT Wana Wisata Indah), perangkat desa, masyarakat, dan wisatawan. Analisis dilakukan dengan pendekatan SWOT yang diperkuat oleh matriks IFE dan EFE, di mana bobot dan rating ditetapkan melalui triangulasi sumber dan validasi ahli. Hasil penelitian menunjukkan bahwa ketiga aspek 4A (attraction, amenity, ancillary) telah memadai, namun aksesibilitas masih menjadi kendala utama. Dari enam dimensi wellness, kesehatan fisik dan lingkungan telah terpenuhi dengan baik, sementara dimensi mental dan spiritual belum terprogram secara terstruktur. Total skor IFE 3,04 dan EFE 2,93 menempatkan TWA Gunung Pancar pada kuadran I, sehingga strategi pertumbuhan agresif diperlukan dengan memanfaatkan kekuatan alam dan peluang kolaborasi untuk meningkatkan daya saing sebagai destinasi wellness tourism berkelanjutan.